h y Karin Zimmer, Jan-Henning Ehm, Susanne Kuger, Jan Lonnemann, Jolika Schulte, Dominique Rauch, Marcus Hasselhorn. - Zimmer, Karin; Ehm, Jan-Henning.; Kuger, Susanne; Lonnemann, Jan.; Schulte, Jolika; Rauch, Dominique; Hasselhorn, Marcus; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2025)
This is an Open access book. Language promotion in German day-care centres is placed on an evidence-based foundation in this study: After a comprehensive review of sources from scientific literature as well as materials from public and civil society actors and the general public, it analyses which language support measures are used in Germany, who they are aimed at, how they are implemented and what information is available on their effectiveness. The result is a structured, systematic overview of the language support measures used in child day-care centres in Germany in the research period from 1949 to 2017.
Background -- Objectives -- Review methodology -- Information on the sources -- Map of Interventions (Research Question 1) -- Effectiveness of the Interventions (Research Question 2) -- Concluding remarks -- References -- Appendix.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Early childhood education; Education; Early Childhood Education; Education